Independent and joint associations of volume and intensity of physical activity on cognitive impairment among middle-aged and elderly Chinese adults: A national longitudinal study - Wei Yin; Yan Han; Hongmei Sun (PLoS ONE, 2025)
Background The objective of this study was to explore the longitudinal relationship between the volume and intensity of physical activity (PA) and their combined risk for cognitive impairment (CI). Methods The study included 10,174 participants from the 2011-2018 CHARLS cohort. Pennsylvania and CI were assessed using self-reported questionnaires. Statistical analyses were performed using the Cox regression model. Results After adjusting for all covariates, the risk of CI was 14% lower in subjects with physical activity volume (PAV) ≥600 Metabolic Equivalent of Task (MET)-min/week compared to those with insufficient PA (HR: 0.86). The risk was reduced by 38% for subjects with PAV of 1800−2999 MET-min/week (HR: 0.62). Regarding the intensity of PA, the risk of CI was reduced by 25% for a proportion of 0.25–0.5 of (moderate to vigorous PA) MVPA to PAV (HR: 0.75) compared to a proportion of 0–0.25. Regardless of PAV, the risk of CI was lowest when the proportion of moderate to vigorous PA(MVPA) to PAV was 0.25–0.5, and 0.5–0.75 for the proportion of light-intensity physical activity (LPA) to PAV. Conclusion The PAV 1800−2999 MET-min/week and maintaining a proportion of LPA to PAV of 0.5–0.75, or a proportion of MVPA to PAV of 0.25–0.5, are more effective in reducing the risk of CI. Policy implications should prioritize tailored physical activity strategies for individuals over 65, emphasizing low-intensity activities, safe high-intensity training, and the development of accessible urban facilities, in line with WHO guidelines.